Structure and folding of the Tetrahymena telomerase RNA pseudoknot - Cash, Darian D. (Nucleic Acids Res, 2017)
Telomerase maintains telomere length at the ends of linear chromosomes using an integral telomerase RNA (TER) and telomerase reverse transcriptase (TERT). An essential part of TER is the template/pseudoknot domain (t/PK) which includes the template, for adding telomeric repeats, template boundary element (TBE), and pseudoknot, enclosed in a circle by stem 1. The Tetrahymena telomerase holoenzyme catalytic core (p65-TER-TERT) was recently modeled in our 9 Å resolution cryo-electron microscopy map by fitting protein and TER domains, including a solution NMR structure of the Tetrahymena pseudoknot. Here, we describe in detail the structure and folding of the isolated pseudoknot, which forms a compact structure with major groove U•A-U and novel C•G-A(+) base triples. Base substitutions that disrupt the base triples reduce telomerase activity in vitro. NMR studies also reveal that the pseudoknot does not form in the context of full-length TER in the absence of TERT, due to formation of a competing structure that sequesters pseudoknot residues. The residues around the TBE remain unpaired, potentially providing access by TERT to this high affinity binding site during an early step in TERT-TER assembly. A model for the assembly pathway of the catalytic core is proposed.